REGULASI LINGKUNGAN DALAM MITIGASI DAMPAK PERUBAHAN IKLIM PADA UMKM DI KOTA BATAM: ANALISI KEBIJAKAN DAN REKOMENDASI - Winda Fitri; Despin Zainuddin; Winsherly Tan (Fakultas Ilmu Sosial dan Humaniora, 2025)
This research aims to analyze the effectiveness of legal regulations in providing legal protection for Micro, Small, and Medium Enterprises (MSMEs) in Batam City against the impacts of climate change. The method used is a normative juridical approach with qualitative analysis of secondary data, including primary legal materials (such as Law No. 32/2009 on Environmental Protection and Management and NDC documents), secondary materials (scientific literature, policies), and tertiary materials (legal dictionaries). The research findings indicate that national and regional regulations have not explicitly accommodated the protection of MSMEs from climate risks. A significant gap exists between macro policy and local implementation, where MSMEs face barriers in accessing incentives, environmentally friendly technology, and participating in policy formulation. The principle of climate justice is also not yet integrated into regulations, meaning policies tend not to favor the limited adaptive capacity of MSMEs. The research recommends the reformulation of inclusive sectoral regulations, such as the drafting of specific implementing regulations for MSMEs under Law No. 32/2009, harmonization between central and regional governments, and increased multi-stakeholder collaboration. Local governments are encouraged to adopt local incentives, mentoring schemes, and integrate MSMEs into climate action plans. Thus, this research emphasizes the urgency of an adaptive, participatory, and just legal approach to strengthen MSME resilience amidst the climate crisis.